Bone marrow granulomas in mononucleosis. Issue 738 (April 1987) - Fiala, M.; Colodro, I.; Talbert, W.; Ellis, R.; Chatterjee, S.
Abstract : Two patients with mononucleosis, one due to cytomegalovirus (CMV), and the other due to Epstein-Barr virus (EBV), presenting with high fever, malaise and hepatitis, had granulomas in the bone marrow but not in the liver. In patients who have unexplained fever, bone marrow granulomas may be a clue to CMV or EBV infection and need not initially raise the fear of prognostically more severe illness.